2014
DOI: 10.1027/1618-3169/a000262
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Working Memory Is All Fun and Games

Abstract: We developed a novel four-dimensional spatial task called Shapebuilder and used it to predict performance on a wide variety of cognitive tasks. In six experiments, we illustrate that Shapebuilder: (1) Loads on a common factor with complex working memory (WM) span tasks and that it predicts performance on quantitative reasoning tasks and Ravens Progressive Matrices (Experiment 1), (2) Correlates well with traditional complex WM span tasks (Experiment 2), predicts performance on the conditional go/no go task (Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Most gamified assessments were validated successfully. Wii Tests [ 21 ], Shapebuilder [ 37 ], The Great Brain Experiment [ 32 , 39 ], BAM-COG [ 28 ], and Tap the Hedgehog [ 27 ] were all found to produce output measures/scores that correlated fairly well with their non–gamelike counterparts, though mixed-domain measures were an issue (see Supplementary Table 1 in Multimedia Appendix 2 for full details of all games). Validation studies varied in their design, and some studies reported complex correlations between gamified and nongamified tasks with multiple outputs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most gamified assessments were validated successfully. Wii Tests [ 21 ], Shapebuilder [ 37 ], The Great Brain Experiment [ 32 , 39 ], BAM-COG [ 28 ], and Tap the Hedgehog [ 27 ] were all found to produce output measures/scores that correlated fairly well with their non–gamelike counterparts, though mixed-domain measures were an issue (see Supplementary Table 1 in Multimedia Appendix 2 for full details of all games). Validation studies varied in their design, and some studies reported complex correlations between gamified and nongamified tasks with multiple outputs.…”
Section: Resultsmentioning
confidence: 99%
“…Validation studies varied in their design, and some studies reported complex correlations between gamified and nongamified tasks with multiple outputs. However, sample correlations from some of the simpler validation studies suggest intertask correlations of 0.45-0.60 [ 28 , 37 , 39 , 63 ]. Broadly speaking, these were well-designed and well-powered studies, and together, they provide encouraging evidence that cognitive tests can be gamified and still be useful as a research tool.…”
Section: Resultsmentioning
confidence: 99%
“…It can eliminate the potential influences of verbal proficiency by requiring the participants to recollect unrelated letters rather than sentence-final words. Compared to extensive involvement of the experimenter in the reading span task, the OSPAN is less prone to human error and variation in performance due to differential instructions as well (Atkins et al, 2014). Zhou et al (2016) adopted both the L2 reading span task and the OSPAN task to explore whether WMC affects the processing of subject- and object-extraction by Chinese learners of English.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is increasing evidence that intelligence is accurately measured via games, or game-based assessments [84,85,86,87]. By applying machine learning algorithms to large numbers of data points collected during game play, such assessments achieve accuracy with shorter assessment time, making them particularly suitable to deliver comprehensive assessments of several characteristics such as personality and intelligence.…”
Section: The Future Of Personality and Intelligencementioning
confidence: 99%